Assessing the air quality of megacities during the COVID-19 pandemic lockdown: a case study from Makkah City, Saudi Arabia - Morsy, Essam (Arab J Geosci, 2021)
Many countries are concerned about how concentrations of outdoor air pollutants have decreased due to control measures aftermath of the COVID-19 outbreak. In Saudi Arabia, the measures started with suspending entry to Saudi Arabia on February 27, 2020, and ended with full prevention of Saudis for outdoor movement on April 2, 2020, until the back return to normal life by the start of September 2020. These measures are expected to impact air quality levels during this period by decreasing the concentrations of air pollutants. This paper investigates the major trends of ambient air pollution (SO(2), NO(2), CO, O(3), and PM(10)), and maps the spatiotemporal variability of air pollutants in Makkah city, using a continuous air quality monitoring network (6 sites) during the pre-pandemic period. Findings indicate the presence of a significant decrease of concentration rates during the lockdown period, compared with the pre-pandemic period, by 26.34% for SO(2), 28.99% for NO(2), 26.24% for CO, 11.62% for O(3), and 30.03% for PM(10). Therefore, the vehicular traffic activities represent 25–30% of the total air pollution load in Makkah city. The COVID-19 lockdown conditions in Makkah provide a unique opportunity to evaluate the impact of the reduction of vehicular traffic activities on the air quality levels of Makkah city and similar mega-cities and introduce credible solutions to improve the conditions of the ambient environment and air quality in such settings.